Composite catalysts of Pt/SO42--ZrO2 and Pt/WO3-ZrO2 for produce octane enhancers for the gasoline pool - Busto, Mariana (2012)
Isomerization-cracking of long paraffins to produce octane enhancers for the gasoline pool is a complex refinery operation that needs simultaneous adjustment of the molecular size of the feed (cracking) and skeletal branching (isomerization). As both reactions are acid-catalyzed it is very difficult to adjust the acidity distribution of a single catalyst to have a proper balance. In this work the used catalyst is a mixture of an isomerization catalyst (Pt/WO3?ZrO2) (PtWZ) and a cracking catalyst (Pt/SO4 2−?ZrO2) (PtSZ), working at the same reaction conditions. The tests were performed using n-hexadecane as a model feedstock. The screening of pressure and temperature conditions indicates that the best match for both catalysts is 20 atm and 225 °C. Stable activity levels for both catalysts can only be achieved at a H2/n-C16 ratio of 10. An adequate space velocity for increasing the yield to iC5?9 and preventing consecutive cracking is 18.4 h−1. At this process conditions mixtures (PtWZ+PtSZ) that contain 25% or 50% PtSZ have a better product distribution, with the maximum displaced to higher carbon numbers, with a reduced yield to isobutane and light gasses. Operation points lie on a monotonic curve of octane number gain (ΔRON) as a function of the yield of light gasses (C1?4) that indicates that RON gains can only be obtained at the expense of the liquid yield.